2022
DOI: 10.3390/genes13050726
|View full text |Cite
|
Sign up to set email alerts
|

Complete Mitochondrial Genomes of Five Racerunners (Lacertidae: Eremias) and Comparison with Other Lacertids: Insights into the Structure and Evolution of the Control Region

Abstract: Comparative studies on mitochondrial genomes (mitogenomes) as well as the structure and evolution of the mitochondrial control region are few in the Lacertidae family. Here, the complete mitogenomes of five individuals of Eremias scripta (2 individuals), Eremias nikolskii, Eremias szczerbaki, and Eremias yarkandensis were determined using next-generation sequencing and were compared with other lacertids available in GenBank. The circular mitogenomes comprised the standard set of 13 protein-coding genes (PCGs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Many tick species share great morphological similarities and therefore group into species complexes until differentiating characters can be described [ 22 ]. The mitochondrial genome (mitogenome) is a reliable marker for cryptic species identification, phylogenetic studies, and population genetics analysis, and has been widely used in animals [ 23 , 24 , 25 , 26 , 27 , 28 ], including in ticks [ 7 , 21 , 29 ]. In recent years, the number of sequenced mitogenomes of Ixodidae species has increased significantly, but the mitogenome studies on parasitic ticks of giant pandas have only been performed for three Haemaphysalis species [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many tick species share great morphological similarities and therefore group into species complexes until differentiating characters can be described [ 22 ]. The mitochondrial genome (mitogenome) is a reliable marker for cryptic species identification, phylogenetic studies, and population genetics analysis, and has been widely used in animals [ 23 , 24 , 25 , 26 , 27 , 28 ], including in ticks [ 7 , 21 , 29 ]. In recent years, the number of sequenced mitogenomes of Ixodidae species has increased significantly, but the mitogenome studies on parasitic ticks of giant pandas have only been performed for three Haemaphysalis species [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gene reversal, gene transposition, and tandem duplications with subsequent random gene loss have been proved to be possible causes of changes in the mitochondrial gene order in deep‐sea mussels (Zhang et al., 2021 ). In contrast, the mitochondrial gene order is conserved in vertebrates (Kundu et al., 2018 ; Tian & Guo, 2022 ). Our study supports the conclusion drawn in vertebrates, as revealed by the observation that the mitochondrial gene order was almost identical among different species of lacertid lizards, with inter‐specific differences reflected only in whether some genes are located on the heavy or light strand.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial genome (mitogenome) is increasingly popular in various scientific disciplines such as animal comparative genomics, molecular evolution, phylogenetics, and biogeography [ 1 , 2 , 3 , 4 ]. In comparison with its individual genes widely used in phylogenetics and biogeography, the mitogenome can be more phylogeny-informative and provide multiple genome-level characteristics such as gene order and rearrangements, RNA secondary structures, and modes of control of replication and transcription [ 5 , 6 , 7 , 8 , 9 ]. The mitogenome of insects is a small double-stranded circular molecule of 14–20 kb in size, containing 37 genes including 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNA), and two ribosomal RNA genes (12S and 16S rRNA) [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%